2019
DOI: 10.1042/bsr20181995
|View full text |Cite
|
Sign up to set email alerts
|

AMPK is associated with the beneficial effects of antidiabetic agents on cardiovascular diseases

Abstract: Diabetics have higher morbidity and mortality in cardiovascular disease (CVD). A variety of antidiabetic agents are available for clinical choice. Cardiovascular (CV) safety assessment of these agents is crucial in addition to hypoglycemic effect before clinical prescription. Adenosine 5′-monophosphate-activated protein kinase (AMPK) is an important cell energy sensor, which plays an important role in regulating myocardial energy metabolism, reducing ischemia and ischemia/reperfusion (I/R) injury, improving he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 171 publications
0
34
0
Order By: Relevance
“…Studies showed that AMPK deletion promoted mitochondrial fragmentation in ECs by inhibiting the autophagy-dependent degradation of DRP1 [ 105 ]. Numerous anti-diabetic agents may improve endothelial function by targeting AMPK to impact mitochondrial dynamics [ 227 ]. Clusterin, which exerts beneficial effects in ECs under diabetic conditions (both type 1 and type 2), inhibits mitochondrial fragmentation while activating AMPK [ 228 ].…”
Section: Cardio-metabolic Diseasesmentioning
confidence: 99%
“…Studies showed that AMPK deletion promoted mitochondrial fragmentation in ECs by inhibiting the autophagy-dependent degradation of DRP1 [ 105 ]. Numerous anti-diabetic agents may improve endothelial function by targeting AMPK to impact mitochondrial dynamics [ 227 ]. Clusterin, which exerts beneficial effects in ECs under diabetic conditions (both type 1 and type 2), inhibits mitochondrial fragmentation while activating AMPK [ 228 ].…”
Section: Cardio-metabolic Diseasesmentioning
confidence: 99%
“…AMPK activation furthermore reduces hepatic lipogenesis and increases hepatic β-oxidation and reduces adipocyte lipolysis and lipogenesis, which has made it an attractive drug target for the treatment of type 2 diabetes [50]. Despite its obvious regulation of lipid metabolism in the liver and adipose tissue, AMPK activation has been specifically associated with the beneficial effects of some anti-diabetic drugs on cardiovascular diseases [51]. In addition, AMPK activation has been proposed as a therapeutic target in heart failure [52], where its cardioprotective role is thought to be due to mechanisms beyond regulation of cellular energy metabolism [53].…”
Section: Structure and Function Of Ampkmentioning
confidence: 99%
“…AMPK, which is widely distributed in various cells and organs as a heterotrimeric protein complex, consists of 3 subunits including catalytic α (66kDa) subunits, regulatory β (38 kDa) and γ (38 kDa) subunits which occur as multiple isoforms (α1/α 2; β1/β2; γ1/γ2/γ3) encoded by distinct genes [8]. Compelling evidence has indicated that activated AMPK ameliorates myocardial ischemiareperfusion injury (IRI) [8][9][10]. while the absence of AMPK may promote IRI in an aged heart [11].…”
Section: Introductionmentioning
confidence: 99%